2 answers:
9+6=15 and 15-12=3 so this =3 the -(-6) becomes positive
Remember to follow the Left -> Right rule.
First, solve 9 - (-6). Remember that two negatives = one positive:
9 - (-6) = 9 + 6 = 15
Now solve:
15 - 12 = 3
3 is your answer
<em>~Rise Above the Ordinary, Senpai</em>
You might be interested in
do not enter the link it may be a virus
Answer:
3/8
Step-by-step explanation:
Answer:
The awnser for that is -2, my friend
Answer:
1
Step-by-step explanation:
Answer:
ok
Step-by-step explanation: